2018
DOI: 10.1117/1.jbo.23.2.020902
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography for the diagnosis of malignant skin tumors: a meta-analysis

Abstract: Optical coherence tomography (OCT) is an emergent imaging tool used for noninvasive diagnosis of skin diseases. The present meta-analysis was carried out to assess the accuracy of OCT for the diagnosis of skin cancer. We conducted a systematic literature search though EMBASE, Medline, PubMed, the Cochrane Library, and Web of Science database for relevant articles published up to June 6, 2017. The quality of the included studies was assessed using the QUADAS-2 tool and the Oxford Levels of Evidence Scale. Stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 61 publications
(164 reference statements)
0
21
0
3
Order By: Relevance
“…Addressing the in vivo use of OCT Xiong et al carried out a meta-analysis to assess the accuracy of OCT for the diagnosis of skin cancer, in the in vivo, non-invasive setting and not on excised tissue samples. This meta-analysis reported that OCT appeared to be useful for the detection of BCC and SCC and was a valuable diagnostic method when screening for early skin cancers [26]. In the future, the combination of ex vivo and in vivo CLSM in just one device could be a perfect diagnostic tool for the pre-and intraoperative setting.…”
Section: Discussionmentioning
confidence: 98%
“…Addressing the in vivo use of OCT Xiong et al carried out a meta-analysis to assess the accuracy of OCT for the diagnosis of skin cancer, in the in vivo, non-invasive setting and not on excised tissue samples. This meta-analysis reported that OCT appeared to be useful for the detection of BCC and SCC and was a valuable diagnostic method when screening for early skin cancers [26]. In the future, the combination of ex vivo and in vivo CLSM in just one device could be a perfect diagnostic tool for the pre-and intraoperative setting.…”
Section: Discussionmentioning
confidence: 98%
“…1220 Additionally, OCT can accurately detect depth. 2123 However, each technology, when used independently, cannot provide comprehensive information to guide both diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Dubois et al [39] have used line-field confocal optical coherence tomography (LC-OCT) for high resolution and non-invasive imaging of human skin, which significantly improves accuracy for diagnosis of skin tumors resulting in a reduced number of biopsies. Xiong et al [40] used optical coherence tomography (OCT), imaging tool for non-invasive diagnosis of skin diseases i.e., basal cell carcinoma (BCC), squamous cell carcinoma (SCC), actinic keratosis, and malignant melanoma. The authors in [41] have used a real-time magneto-motive optical Doppler tomography (MM-ODT), imaging method for detection of superparamagnetic iron oxide (SPIO) magnetic nanoparticles implanted into melanoma tissue melanoma tissues and used multi-threaded programming techniques for real-time imaging and optimized the signal path.…”
Section: Literature Surveymentioning
confidence: 99%